Tingkat Pengetahuan Masyarakat Terhadap Obat Analgesik Pada Swamedikasi Untuk Mengatasi Nyeri Akut - Asyraf Vivaldi Wardoyo; Rasmi Zakiah Oktarlina (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Analgesic drugs or painkillers are one of the drugs that are often used independently by the community without a doctor's prescription, this causes the emergence of several side effects of analgesi drugs. Analgesic drugs commonly used by the public are nonopioid analgesic drugs such as aspirin, mefenamic acid and paracetamol because nonopioid analgesic drugs are not as addictive as opioid analgesic drugs. Analgesic drugs have side effects including hypersensitivity reactions, stomach and intestinal disorders, damage to the kidneys, and can cause liver damage if consumed in excessive doses. Several studies have shown that the level of public knowledge is closely related to the rational use of pain medications or analgesics. The higher the level of knowledge, the better and more appropriate in using analgesic drugs and vice versa, so that the more rational the community uses analgesic drugs, the fewer side effects that can arise. Self-medication or self-medication is a community effort to deal with pain that occurs mainly acutely or suddenly. Self medication can be a source of medication errors due to the limited knowledge of the community about drugs and their use. If self-medication can be carried out correctly by the community, then self-medication can have a large positive impact on both the community itself and the government in terms of national health care